Four new species of coral crabs belonging to the genus Tetralia Dana, 1851 (Crustacea, Decapoda, Brachyura, Tetraliidae) - Trautwein, Sandra E. (Zootaxa, 2007)
Four new species of Tetralia Dana, 1851, are described from the west Pacific. Like the six previously described sister species, the new species (Tetralia aurantistellata, T. brengelae, T. brunalineata, and T. ocucaerulea) are obligate symbionts of scleractinian corals belonging to the genus Acropora. The new species are described herein, placing particular emphasis on live color patterns.